The Dynamic Oval Pupil - Bremner, Fion D.; Drapkin, Allan J. (Frontiers in Neurology, 2019)
The dynamic oval pupil is defined and its distinction from corectopia, as well as their different clinical significance is proposed. A literature search for instances presenting this condition yielded only twenty such cases with enough clinical data. A review of these cases allows us to draw some tentative conclusions regarding the most likely anatomical location for its causative lesion and the pathophysiological mechanism responsible for its occurrence.